DC electrical degradation of YSZ: Voltage‐controlled electrical metallization of a fast ion conducting insulator. Issue 5 (20th January 2020) - Alvarez, Ana; Dong, Yanhao; Chen, I‐Wei
Abstract: DC electrical degradation as a form of dielectric and resistance breakdown is common in thin‐film devices including resistance‐switching memory. To obtain design data and to probe the degradation mechanism, highly accelerated lifetime tests (HALT) are often conducted at higher temperatures with thicker samples. While the mechanism is well established in semiconducting oxides such as perovskite titanates, it is not in stabilized zirconia and other fast oxygen‐ion conductors that have little electronic conductivity. Here we model the mechanism by an oxygen‐driven, transport‐limited, metal‐insulator transition, which finds support in rich experimental observations—including in situ videos and variable temperature studies—of yttria‐stabilized zirconia. This demonstrates that although (electro) reduction does not appreciably alter oxygen stoichiometry in stabilized zirconia, which is fixed by the dopant concentration, it can still raise the chemical potential of electrons enough to eventually reach the conduction‐band level, thereby triggering the insulator‐to‐metal transition and resistance degradation. These results are contrasted with the findings in semiconducting titanates and resistance memory, and to provide new insight into ceramic processing with extremely rapid heating and cooling such as flash sintering and melt processing.